RELATIONSHIP BETWEEN ENTREPRENEURIAL TEAM AND GROWTH OF SMALL AND MEDIUM MANUFACTURING ENTERPRISES IN KENYA - Mwaniki, Zipporah; Ngugi, Patrick; Nyang'au, Samson (International Journal of Entrepreneurship and Project Management, 2022)
Purpose: The purpose of this study was to assess the relationship between entrepreneurial team and growth of small and medium manufacturing enterprises in Kenya. Methodology: The study adopted a descriptive survey design. The target population was 422 manufacturing SMEs in Nairobi County who are members of Kenya Association of Manufacturers. Nairobi County was purposively selected. Both stratified and simple random sampling was used to select a representative sample. Both primary and secondary data collection techniques were employed. A Pilot study was conducted on 20 manufacturing SMEs in Kiambu County to establish and improve on the validity and reliability of research instruments. Data collected was coded and stored in tabular form using Microsoft Excel. Data was analyzed using both quantitative and qualitative data analysis methods. Quantitative data was analyzed using Statistical Package for Social Sciences (SPSS) Version 25 software through descriptive statistics (measures of central tendency and measures of dispersion). Data was presented through Tables. Results: The study found out that the there was a significant positive relationship between entrepreneurial team and growth of small and medium enterprises. The conclusion from the results is that that 23.8% of growth of small and medium enterprises in Kenya is explained by entrepreneurial team. Unique contribution to theory, practice and policy: The study recommended that the government should formulate supportive policies for entry, survival and growth of manufacturing SMEs such as favorable terms and conditions for accessing finance, entrepreneurial education and training, research and development and markets.